MANUNGGALING KAWULA GUSTI : KONSEP MANUSIA SEMPURNA DALAM PERSPEKTIF KEJAWEN BONOKELING - Jeyhan Yuganof; Kholil Lur Rochman (BHAKTISIFA: Jurnal Pengabdian kepada Masyarakat, 2025)
This article discusses the concept of Manunggaling Kawula Gusti in the Kejawen tradition and its relevance for indigenous counselors in achieving the perfect human. Manunggaling Kawula Gusti describes the unity between humans and God, which serves as a spiritual foundation in individual self-development. Through this approach, indigenous counselors can integrate deep local values into counseling practices, thereby creating a more holistic experience for clients. This research uses qualitative methods with interviews and literature analysis to explore how Kejawen principles can be applied in the context of modern counseling. Research results show that a deep understanding of Manunggaling Kawula Gusti can help counselors facilitate the spiritual awakening process of clients, as well as support them in achieving mental and emotional well-being. This article is expected to contribute to the development of counseling practices that are more contextual and relevant to local cultural values.